The reduction of body mass index and risk of incidence of cardiovascular events in the elderly population. (24th May 2021) - Park, JW; Yang, PS; Yu, HT; Kim, TH; Jang, ES; Pak, HN; Lee, MH; Joung, BY
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Obesity is known to be risk factor for incidence of cardiovascular (CV) events. However, the association between the reduction of body mass index (BMI) and incidence of cardiovascular event is not well established in elderly Asian population. Methods: From the National Health Insurance Service-Senior (≥60 years) cohort from 2002 to 2013, 13, 038 participants over 75 years old without baseline comorbidities (mean age: 78.4 ± 3.2 years 5243 (40.2%) male) were included in this study. We measured the change of BMI from first to second visit for health check-up within mean 23.6 ± 5.8months of follow-up. We categorized the reduction of BMI as five group according to the amount of change in BMI in overall patients (group 1: BMI change <-10%, group 2: -10%≤BMI change<-3%, group 3: -3% ≤ BMI change < 3%, group 4: 3% ≤BMI change < 10%, group 5: 10% ≤BMI change). We investigated the influence of change in BMI on the incidence of new-onset AF, stroke, acute myocardial infarction (MI), and CV mortality Results: In the overall patients, new-onset AF, stroke, acute MI, and CV death was occurred in the 494 patients (3.5%), 775 patients (5.9%), 16 patients (0.1%), and 458 patients (3.5%) respectively. The Kaplan-Meier curve showed significant cumulative incidence rate of CV death in group 1 (Log rank p < 0.001). The multivariate cox regression after adjusting for compound clinical covariates showed the risk of stroke (HR 1.43, 95% CI [1.09-1.89], p = 0.01) and CV death (HR 2.06, 95% CI [1.49-2.84] were significant higher in the group 1 as compared with group 3. In the high BMI (≥25) group, the risk of AF was significant higher in the group 5 as compared with group 3 (HR 2.38, 95% CI [1.02-5.54], p = 0.04). In contrast, the risk of stroke (HR 1.70, 95% CI [1.07-2.71], p = 0.02) and CV death (HR 3.27, 95% CI [1.66-6.41], p < 0.001) was significant higher in the group 1 than in group 3. Conclusions: In the elderly Asian population over 75 years old, the reduction of body weight affected worse effect on the incidence of stroke and CV death in overall patient and high BMI (≥25) group. It needs careful consideration to reduce BMI in the elderly Asian population even with high BMI (≥25) for purpose of CV events.